2006
DOI: 10.1136/bmj.38852.479907.7c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of off-pump coronary artery bypass surgery on clinical, angiographic, neurocognitive, and quality of life outcomes: randomised controlled trial

Abstract: Objective To compare the clinical, angiographic, neurocognitive, and quality of life outcomes of off-pump coronary artery bypass surgery with conventional coronary artery bypass grafting surgery using cardiopulmonary bypass. Design Randomised controlled clinical trial. Setting Tertiary cardiothoracic centre in Middlesex, England. Participants 168 patients (27 women) requiring primary isolated coronary artery bypass grafting surgery. Interventions Patients were randomised to conventional coronary artery bypass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
3
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(125 citation statements)
references
References 52 publications
7
110
3
5
Order By: Relevance
“…Ascione and Angelini (5) discussed the dilemma faced by many cardiac surgeons who perform CABG. On one hand, the literature is replete with studies that emphasize the potential for reducing postoperative morbidity and length of stay with OPCAB surgery (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24); on the other hand, there is continued concern regarding intraoperative myocardial ischemia, inadequate revascularization and the need for early revascularization (5,8,23,(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Ascione and Angelini (5) discussed the dilemma faced by many cardiac surgeons who perform CABG. On one hand, the literature is replete with studies that emphasize the potential for reducing postoperative morbidity and length of stay with OPCAB surgery (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24); on the other hand, there is continued concern regarding intraoperative myocardial ischemia, inadequate revascularization and the need for early revascularization (5,8,23,(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…In this questionnaire eight scales cover physical, mental, and social well-being (28). One study found a significantly higher score among CCABG-patients in one of the eight scales ("Role emotional") in contrast to another study who favoured OPCAB patients in the dimension "Social Relationships", using another questionnaire (29,30). In general, few significant inter-group differences have been found, given the multiple tests being performed.…”
Section: Quality Of Lifementioning
confidence: 80%
“…The incidence of pre-existing cognitive impairment in patients undergoing cardiac surgery is 35-45% (Hogue et al, 2006;Silbert et al, 2007) and the incidence of deterioration of cognitive function after cardiac surgery varies at a rate of 25-80% (Rasmussen et al, 2001). These study results depend on the type of surgery, the cardiac patients being studied, the method to determine POCD, the surgical practice, the protocols implemented by individual medical centres and surgical teams and the post-operative time that cognitive assessment is made (Al Ruzzeh et al, 2006). The logical conclusion from these studies, as summarized in the review of Taggart et al is the avoidance of these types of surgical operations whenever possible (Taggart & Westaby, 2001).…”
Section: Association With Surgical Operationsmentioning
confidence: 99%